Isolepis levynsiana, a new name for Cyperus tenellus (Cyperaceae) / A. M. Muasya; D. A. Simpson; E. Smets - Muasya, A. Muthama; Simpson, David a.; Smets, Erik (2007)
The recently published name Isolepis tenella (L.f) Muasya & D. A. Simpson is illegitimate, because there exists an earlier homonym. A new name, I. levynsiana Muasya & D. A. Simpson, is proposed for Cyperus tenellus
Keywords: Cyperaceae; Cyperus